Tracheal localization of inflammatory myofibroblastic tumor in adults: A case report - Oluić Branislav; Vešović Radomir; Lončar Zlatibor; Stojšić Jelena; Mujović Nataša; Nikolić Dejan (Vojnosanitetski Pregled)
Introduction. Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm. This disease, of unknown etiology, runs an unpredictable course. Its definitive diagnosis calls for a detailed histopathological analysis including immunohistochemistry. Microscopically, IMT is composed of myofibroblastic spindle and inflammatory cells in different proportions. It presents infrequently in adults with nonspecific symptomatology. The presence of IMT is described in every anatomical region but the tracheal one is especially uncommon. Case report. A 41- year-old female patient checked into our institution due to exacerbation of asthma-like symptoms such as shortness of breath, cough and exertion intolerance. She was originally treated as the asthmatic patient with the bronchodilator therapy with no success. Chest x-ray done during one of the outpatient follow-up appointments pointed to a suspected change in the tracheal distal part. After her admission to our institution, the following diagnostic procedures were performed: spirometry, chest computed tomography (CT) scan, chest magnetic resonance imaging (MRI) and bronchoscopy and the change in tracheal distal third was confirmed. Right-sided thoracotomy with mobilization of lung, tracheal resection and termino-terminal (T-T) anastomosis was undertaken. Subsequent histopathological analysis of surgically removed afflicted tracheal part of them trachea including immunohistochemistry enabled us to definitively of diagnose IMT. Four years after surgical resection, the patient showed no recidivism of illness. Conclusion. Definitive IMT diagnosis requires the detailed diagnostic tests, most importantly, an adequate histopathological analysis including immunohistochemistry. Complete surgical resection is the treatment of choice in case of IMT. Further monitoring of patients is necessary due to a risk of recurrence.